Theaflavin-3,3′-Digallate Suppresses Biofilm Formation, Acid Production, and Acid Tolerance in Streptococcus mutans by Targeting Virulence Factors - Wang, Sa; Wang, Yuan; Wang, Ying; Duan, Zhuhui; Ling, Zongxin; Wu, Wenzhi; Tong, Suman; Wang, Huiming; Deng, Shuli (Frontiers in Microbiology, 2019)
As one of the most important cariogenic pathogens, Streptococcus mutans has strong abilities to form biofilms, produce acid and tolerate acid. In present study, we found that theaflavin-3,3’-digallate (TF3) had an inhibitory effect on S. mutans UA159 in vitro. Visualized by field emission-scanning electron microscopy (FE-SEM), the suppressed formation of S. mutans biofilms grown with TF3 at sub-inhibitory concentrations could be attributed to the reduced biofilm matrix, which was proven to contain glucans and extracellular DNA (eDNA). Glucan-reduced effect of TF3 was achieved by down-regulating expression levels of gtfB, gtfC, and gtfD encoding glucosyltransferases. Besides, TF3 reduced eDNA formation of S. mutans by negatively regulating lrgA, lrgB, and srtA, which govern cell autolysis and membrane vesicle components. Furthermore, TF3 also played vital roles in antagonizing preformed biofilms of S. mutans. Bactericidal effects of TF3 became significant when its concentrations increased more than two-fold of minimum inhibitory concentration (MIC). Moreover, the capacities of S. mutans biofilms to produce acid and tolerate acid were significantly weakened by TF3 at MIC. Based on real-time PCR (RT-PCR) analysis, the mechanistic effects of TF3 were speculated to comprise the inhibition of enolase, lactate dehydrogenase, F-type ATPase and the agmatine deiminase system. Moreover, TF3 has been found to downregulate LytST, VicRK, and ComDE two component systems in S. mutans, which play critical roles in the regulatory network of virulence factors. Our present study found that TF3 could suppress the formation and cariogenic capacities of S. mutans biofilms, which will provide new strategies for anti-caries in the future.